➡Content Quality⬅
NO SPAM❎
v = u + at
Q1) Prove this with the help of graph.
Q2) Prove this without the help of graph
9th class CBSE
Answers
Answered by
7
Hi there !!
Thanks for the question :)
Graphical method to prove the second equation of motion is in the attachment :)
The method without graph ,
Down here ⬇️⬇️
We know that ,
![a = \frac{v - u}{t} a = \frac{v - u}{t}](https://tex.z-dn.net/?f=a+%3D++%5Cfrac%7Bv+-+u%7D%7Bt%7D+)
where,
a = acceleration
v = final velocity
u = initial velocity
t = time taken
Let us assume acceleration to be a constant
Therefore,
![a = \frac{v - u}{t} \\ = (a) \times (t) = v - u a = \frac{v - u}{t} \\ = (a) \times (t) = v - u](https://tex.z-dn.net/?f=a+%3D++%5Cfrac%7Bv+-+u%7D%7Bt%7D++%5C%5C++%3D+%28a%29+%5Ctimes+%28t%29+%3D+v+-+u)
at = v - u
Transposing u to LHS ,
we have,
at + u = v
or
v = u + at
There we have it ! the 1st equation of motion
Thanks for the question :)
Graphical method to prove the second equation of motion is in the attachment :)
The method without graph ,
Down here ⬇️⬇️
We know that ,
where,
a = acceleration
v = final velocity
u = initial velocity
t = time taken
Let us assume acceleration to be a constant
Therefore,
at = v - u
Transposing u to LHS ,
we have,
at + u = v
or
v = u + at
There we have it ! the 1st equation of motion
Attachments:
![](https://hi-static.z-dn.net/files/dad/e3da6340d5ae9d73e85e6c869157c3c7.jpg)
Anonymous:
hope ye got it :-)
Answered by
11
Hey there !!
____________________________________
Q1) Refer to the attachment for the graph.
From the graph, initial velocity is u (at point A) and then it increases to v (at point B) in time t.
The velocity changes at a uniform rate a.
The initial velocity is represented by OA, the final velocity is represented by BC and the time is represented by OC.
BC – CD = BD represents the change in velocity in time t.
Now, BC = BD + DC = BD + OA
Substituting BC = v and OA = u
v = BD + u
or
BD = v – u ...(1)
As we know, a = Change in velocity / time taken
= BD/AD = BD/OC
Substituting OC = t
a = BD/ t
or
BD = at ...(2)
Using eqⁿ (1) and (2),
v = u + at
____________________________________
Q2) Let 'a' be acceleration.
a = Change in velocity / time taken
Let 'u' be the initial velocity and 'v' be the final velocity of the object. And time taken is donated by 't'.
Now, a = ( v – u ) / t
=> at = v – u
=> v = u + at
____________________________________
Hope my ans.'s satisfactory. (^-^)
____________________________________
Q1) Refer to the attachment for the graph.
From the graph, initial velocity is u (at point A) and then it increases to v (at point B) in time t.
The velocity changes at a uniform rate a.
The initial velocity is represented by OA, the final velocity is represented by BC and the time is represented by OC.
BC – CD = BD represents the change in velocity in time t.
Now, BC = BD + DC = BD + OA
Substituting BC = v and OA = u
v = BD + u
or
BD = v – u ...(1)
As we know, a = Change in velocity / time taken
= BD/AD = BD/OC
Substituting OC = t
a = BD/ t
or
BD = at ...(2)
Using eqⁿ (1) and (2),
v = u + at
____________________________________
Q2) Let 'a' be acceleration.
a = Change in velocity / time taken
Let 'u' be the initial velocity and 'v' be the final velocity of the object. And time taken is donated by 't'.
Now, a = ( v – u ) / t
=> at = v – u
=> v = u + at
____________________________________
Hope my ans.'s satisfactory. (^-^)
Attachments:
![](https://hi-static.z-dn.net/files/d5a/1c557e78fa3dcaad8f265e722eecff10.jpg)
Similar questions